Calcium supplementation improves in vitro salt tolerance of date palm (Phoenix dactylifera L.) - Al-Khateeb, Suliman; Sattar, Muhammad Naeem; Al-Khateeb, Abdullatif; Mohmand, Akbar (Progress in Nutrition, 2021)
Calcium (Ca2+) plays a major role to regulate various physiological and cellular processes. Ca2+ supplementation may activate many downstream responses in plants to regulate their growth, water status, nutrient uptake, cellular metabolism and nutritional balance under saline conditions. In vitro experiments were conducted for investigating the ameliorating effects of calcium under saline conditions in date palm (Phoenix dactylifera L) cultivar, Khalas. The plantlets were subjected to NaCl stress (0, 100 and 200mM) in combination with CaCl2 (0, 5 and 10mM). Ionic concentrations of Ca2+, Mg2+, Na+ and K+ and K+/Na+, Ca2+/Na+, K+/Ca2+ ratios were calculated. Moreover, the growth characteristics (leaf and root number, leaf and root length, leaf and root fresh weight, leaf and root dry weight, and dry weight root/shoot ratios) were also investigated. The number of leaves were improved with the addition of Ca2+, significantly. Similarly, the 10mM Ca2+ significantly enhanced the leaf dry weight. With increasing NaCl levels, the dry weight was affected significantly with the decreasing ionic ratios. However, the supplementation of CaCl2 considerably improved these ionic ratios. With an increase in salinity, the concentrations of Na+, K+, Ca2+ and Mg2+ increased significantly. While K+/Na+ ratios decreased with increasing salt levels. However, the addition of Ca2+ significantly improved K+/Na+ ratios. The transcript expression of NHX1 and HA1 genes was also investigated. The expression of NHX1 and HA1 was increased with increasing NaCl however, the addition of CaCl2 remarkably reduced the expression of both genes. The expression of NHX1 was more prominent in roots than shoots.